Small actions to promote conservation and sustainability - Chris O'Halloran (Conservation Science and Practice)
Abstract In the context of recent anthropogenic climate change and the alarming loss of biodiversity, urgent action is required to safeguard our life‐sustaining ecosystems and implement effective sustainable conservation behavior change strategies. To attend to this concern, the present study explores the efficacy of the evidence‐based Tiny Habits® method in fostering behavior change for sustainability. To this end, a case–control pilot project was conducted with a small cohort of adults randomly divided into two groups: cases and controls. Both groups engaged in a 5‐day online program, selecting and practicing three Tiny Habits recipes daily. The conservation Tiny Habits group focused on sustainable actions, while the control group engaged in non‐conservation activities such as relaxation. The results revealed that practicing the Tiny Habits method resulted in an immediate and sustained increase in conservation actions, with lasting changes (up to 1 month) in the participants' behavior. The mean scores for the intervention group at baseline significantly differed from those immediately and at 1 month after the intervention (p = .0092 and p = .0033). These findings suggest that the Tiny Habits method can be a viable opportunity to cultivate sustainable habits in the long term.